Semaphorin 4C: A Novel Component of B-Cell Polarization in Th2-Driven Immune Responses - Xue, Di; Desjardins, Marylin; Kaufman, Gabriel N.; Béland, Marianne; Al-Tamemi, Salem; Ahmed, Eisha; Tao, Shao; Friedel, Roland H.; Mourad, Walid; Mazer, Bruce D. (Frontiers in Immunology, 2016)
Background: Semaphorins are important molecules in embryonic development and multiple semaphorins have been identified as having key roles in immune regulation. To date, there is little known about Semaphorin 4C (Sema4C) in immune biology. We report for the first time that Sema4C is inducible in human and murine B-cells and may be important for normal B-cell development. Methods: Human Tonsillar B-cells were studied following activation via anti-CD40 antibodies in the presence or absence of representative Th1, Th2, and regulatory cytokines. Murine B-cells from WT and Sema4C-/- mice were similarly stimulated. B-cell phenotyping in WT and Sema4C mutant mice was performed by flow cytometry and lymphoid architecture was studied by immunohistochemistry. Sema4C expression and synapse formation was analyzed by confocal microscopy. Results: Gene Array studies performed on human tonsillar B-cells stimulated to produce IgE revealed that Sema4C was among the top genes expressed at 24 hours, and the only semaphorin to be increased under Th2 conditions. Validation studies demonstrated that human and murine B-cells expressed Sema4C under similar conditions. Sema4C-/- mice had impaired maturation of B-cell follicles in spleens and associated decreases in follicular and marginal zone B-cells as well as impaired IgG and IgA production. In keeping with a potential role in maturation of B-cells, Sema4C was expressed predominantly on CD27+ Human B-cells. Within 72 hours of B-cell activation, Sema4C was localized to one pole in a synapse-like structure, in association with F-Actin, BCR, and Plexin-B2. Cell polarization was impaired in Sema4C-/- mice. Conclusion: We have identified a novel immune semaphorin induced in human and murine B-cells under Th2 conditions. Sema4C appears to be a marker for human memory B-cells. It may be important for B-cell polarization and for the formation of normal splenic follicles.